2022
DOI: 10.3390/agronomy12102433
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-Assisted Immobilization and Health Risks of Potentially Toxic Elements in Wastewater-Irrigated Soil under Brinjal (Solanum melongena) Cultivation

Abstract: Application of wastewater to agricultural soils not only enhances economic benefits but is also considered as a safe disposal option by the administrators. Worldwide, peri-urban horticulture is a common practice for growing vegetables. When agricultural soils are irrigated with wastewater, numerous potentially toxic elements (PTEs) contained therein are bioaccumulated and pose health risks. The presented study aimed to reveal the PTEs, i.e., copper (Cu), cadmium (Cd), nickel (Ni) and lead (Pb) concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…This study provides evidence of the significant improvements in wheat yield and yield components through the application of urea, PM, and zeolites. The probable reason for the higher yield of wheat might be the role of nitrogen in plant metabolism that increases grain yield and the role of zeolite in nutrient retention and slow release in the root zone [49]. The maximum number of grains spike −1 of wheat recorded in our case for UN 120 treatment is in accordance with the findings of Ali et al [50], where they reported a significantly higher number of grains spike −1 from the treatment receiving a full application of chemical fertilizer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides evidence of the significant improvements in wheat yield and yield components through the application of urea, PM, and zeolites. The probable reason for the higher yield of wheat might be the role of nitrogen in plant metabolism that increases grain yield and the role of zeolite in nutrient retention and slow release in the root zone [49]. The maximum number of grains spike −1 of wheat recorded in our case for UN 120 treatment is in accordance with the findings of Ali et al [50], where they reported a significantly higher number of grains spike −1 from the treatment receiving a full application of chemical fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PM with zeolites further increased K uptake, indicating the synergistic effects of organic matter and zeolites in improving K availability for wheat plants. The application of zeolites alone or with organic amendments improved crop quality by enhancing the retention of nutrients in the root zone for plant use [49]. Zeolite regulates the supply of nutrients from both organic and inorganic fertilizers, thereby increasing the efficiency of applied amendments [59].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic activities have boosted the rate of urbanization, industrialization, and agriculture [2], creating a huge pressure on freshwater availability across the globe that may cause water insecurity in the future [3]. Industries generate millions of tons of wastewater with solvents, toxic materials, and heavy metals and discharge them into water bodies untreated [4]. Wastewater constituents, especially heavy metals, and metalloids are of great concern and have destructive effects on the environment and human health [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Industries generate millions of tons of wastewater with solvents, toxic materials, and heavy metals and discharge them into water bodies untreated [4]. Wastewater constituents, especially heavy metals, and metalloids are of great concern and have destructive effects on the environment and human health [4,5]. Small quantities of certain heavy metals, i.e., copper, iron, zinc, and manganese are essential for normal growth and body functions, but higher concentrations of them are highly toxic [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation